Digitization in Catalysis Research: Towards a Holistic Description of a Ni/Al2O3 Reference Catalyst for CO2 Methanation. Issue 8 (9th March 2022) - Weber, Sebastian; Zimmermann, Ronny T.; Bremer, Jens; Abel, Ken L.; Poppitz, David; Prinz, Nils; Ilsemann, Jan; Wendholt, Sven; Yang, Qingxin; Pashminehazar, Reihaneh; Monaco, Federico; Cloetens, Peter; et al.
Abstract: There is considerable motivation in the catalysis community and chemical industry to envision a future where rational catalyst design and targeted chemical process optimization become standard. Achieving this goal for heterogeneous catalysis requires a cultural shift centered around effective research data management. The core elements of modern catalysis research are synthesis, characterization, and testing, while all can be elevated by effective collection, correlation, interoperation, and exploitation of data between disciplines and stakeholders. Here, first steps are made towards a holistic picture of an industrial Ni/Al2 O3 reference catalyst for CO2 methanation. A range of conventional and advanced characterization tools are applied to probe metal particle size and pore characteristics of the support, selected as crucial parameters for catalyst performance. Challenges are shown with respect to current reporting of characterization data and metadata, which ultimately influences the development and reliability of digital twins in catalysis research. Furthermore, the cooperation and combined expertise of diverse research groups from different fields is recognized as essential to deliver meaningful progress towards the digital future of catalysis research. Abstract : The present study introduces an industrial Ni/Al2 O3 catalyst, which is applied as reference material for CO2 methanation in the SPP2080. Detailed characterization and testing studies were performed and discussed in the frame of digitization. The work highlights challenges and open questions on how to report characterization data towards a digital twin.